Innovation Driven By Artificial Intelligence: Exploring The Opportunities And Challenges For Technological And Business Development (Journal of Namibian Studies : History Politics Culture, 2023)
A documentary review was carried out on the production and publication of research papers related to the study of the variable Artificial Intelligence, Innovation and Business Development. The purpose of the bibliometric analysis proposed in this document was to know the main characteristics of the volume of publications registered in the Scopus database during the period 2017-2022, achieving the identification of 568 publications. The information provided by this platform was organized through graphs and figures categorizing the information by Year of Publication, Country of Origin, Area of Knowledge and Type of Publication. Once these characteristics have been described, the position of different authors towards the proposed theme is referenced through a qualitative analysis. Among the main findings made through this research, it is found that China with 107 publications was the country with the highest scientific production registered in the name of authors affiliated with institutions of that nation. The Area of Knowledge that made the greatest contribution to the construction of bibliographic material referring to the study of the variable Artificial Intelligence Innovation and Business Development was Computer Science with 286 published documents, and the Type of Publication most used during the period indicated above were Conference Articles with 36% of the total scientific production.